Study on Evaluation Models of Hidden Curriculum: Illuminative, Case Study and Responsive - Wathani, Diki Hasrul; Arifin, Zainal (Universitas Tanjungpura, 2024)
The purpose of this research is to explore and evaluate the influence of the hidden curriculum on character development among students in a formal educational setting. The background of this study stems from the observation that many essential aspects of education are not covered in the formal curriculum, necessitating further attention in evaluation. The urgency of this research lies in the need to understand the dynamics of the hidden curriculum, which can impact students